Matteucci Effect and Single Domain Wall Propagation in Bistable Microwire under Applied Torsion. Issue 18 (1st August 2021) - Jiménez, Alejandro; Calle, Esther; Fernandez-Roldan, Jose A.; del Real, Rafael P.; Varga, Rastislav; Vázquez, Manuel
Abstract : Systematic experimental results on the Matteucci effect in torsioned magnetostrictive FeSiB microwire are introduced, observed during the propagation of a single domain wall (DW) under the action of axial driving magnetic field, H dr . These data are discussed, reviewing current bibliography models and proposing new perspectives. The unidirectional DW velocity is quantified by voltage induced in tiny pickup coils along the microwire. The Matteucci electromotive force (emf) induced between the microwire's ends is associated with depinning and annihilation of the DW, introducing a new method to measure DW velocity. The emf amplitude is proportional to the DW velocity and the time derivative of the azimuthal magnetization, tailored by applied torsion. The data confirm the existence of net values of azimuthal magnetization and spontaneous torsion induced during fabrication. The clockwise/counterclockwise applied torsion dependence of Matteucci emf and DW velocity are experimentally determined for parallel and antiparallel H dr . Asymmetric behaviors are observed for both, the sense of applied torsion and the direction of H dr . The experimental data are discussed in terms of the magnetoelastic anisotropy introduced by torsion. Through analysis of the DW dynamics, such asymmetric behaviors are interpreted as a magnetochiral effect derived from the change of chirality of the propagating wall. Abstract : The Matteucci effect, ME, in twisted magnetostrictive FeSiB microwire is correlated with the propagation of a single domain wall under an axial driving magnetic field. The asymmetry of both, ME and wall velocity, on the sense of applied torsion and field direction is interpreted in terms of the torsion magnetoelastic anisotropy and the magnetochiral effect of the propagating wall chilarity.